Análise de laje alveolar protendida moldada por fôrma fixa e usando placas de poliestireno expandido - Estudo teórico e experimental - Inforsato, Thiago Bindilatti (2018)
The use of prestressed hollow core slabs has increased significantly and, consequently various productive methods have emerged. These methods do not employ machinery such as extruders or slip former machine. In this research, a production method for prestressed hollow core slab cast into fixed formwork with EPS void former has been detailed and compared with the production that employs machinery. Although there are many producers of hollow core slabs with EPS void former in the Brazilian market, there is still a lack of knowledge about this precast product. Therefore, this research presents a review and recommendations with possible theoretical analyses to be applied within the structural design of this type of precast element, which should also meet the design requirements of the Brazilian codes of practice for cast in situ and precast concrete structures, as well as existent recommendations for prestressed hollow core slabs within the international literature. In order to validate the analytical proposals for design, an experimental program has been carried out comprising standard tests for prestressed hollow core slabs in accordance with international codes of practice and technical literature. Within the experimental program, 15 slabs with heights of 150 mm and were tested under bending and shear forces for simply supported slabs with span of 5,70 meters, comprising 12 shear tests and 3 bending tests. For the shear tests, the length of the span between the applied point load and slab support was varied. Three of the shear tests were carried out for slabs employing transverse reinforcement, while the nine remaining slabs were tested without transverse reinforcement. Complementing the experimental program, three bending tests with concentrated load were also carried out. According to the observed experimental results, the failure mode of the slabs within the shear tests was governed by anchorage failure of the strands. For the bending tests, the experimental results were consistent with the usual bending theory for prestressed members. Finally, for some tested slabs, it has been identified the failure mode was governed by the position of the EPS forming a void within the slab transversal section, which affects the thickness of the top flange. Therefore, an additional study was carried out to evaluate the influence of the cast in place structural topping to increase the bending moment resistance of the prestressed hollow core slab cast into fixed formwork with EPS void former. It is concluded that the use of the cast in place structural topping minimizes possible decreases in the resistant capacity of the prestressed hollow core slab cast into fixed formwork with EPS void former, during the manufacturing process.